SOSIALISASI MANFAAT TANAMAN TOGA DAN PENDAMPINGAN PRAKTEK BUDIDAYA BAGI IBU-IBU PKK DI DESA PANCAKARYA KECAMATAN AJUNG, JEMBER - Kartika Sari, Vega; Budha, Al Sura Tri; Husnawati, Amalia Miranda; Oktavia, Dwi Jannah; Arista, Intan Dwi; Siswanti, Putri Ayu; Windari, Kunis Lili; Maharani, Mifta Dwi; Zalika, Laila Karimatu; Munir, Misbahul; Haryanto, Wasis (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2023)
Lemongrass is a plant which is classified as a medicinal plant or often shortened as tanaman toga in Indonesian language. Lemongrass has numerous benefits. After conducting a survey for several days in Pancakarya, the students of KKN Kolaboratif 82 found that the growth with abundance of lemongrass in the village was not utilized optimally. A lot of lemongrasses was left to dry on the roadside throughout the village. Alongside with this identified problem, the students of KKN Kolaboratif 82 strive to define the solution by doing socialization and accompaniment on planting the lemongrass. This event was held by cooperating with the Village Midwife, the members of PKK, and the cadres of Posyandu. This socialization aims to increase the understanding and awareness in terms of utilizing the potential of lemongrass in Pancakarya. The method which was used in carrying out the activities were problem identification, needs analysis, procurement of socialization as well as practices and assistance in growing lemongrass using polybag. The result evaluation was carried out by implementing a post-test. The results of the activity showed that the understanding of the participants in the socialization of the material provided increased significantly.